The neuropeptide cortistatin attenuates experimental autoimmune myocarditis via inhibition of cardiomyogenic T cell‐driven inflammatory responses. (8th January 2017) - Delgado‐Maroto, Virginia; Falo, Clara P; Forte‐Lago, Irene; Adan, Norma; Morell, Maria; Maganto‐Garcia, Elena; Robledo, Gema; O'Valle, Francisco; Lichtman, Andrew H; Gonzalez‐Rey, Elena; Delgado, Mario
Abstract : Background and purpose: Myocarditis is an inflammatory and autoimmune cardiovascular disease that causes dilated myocardiopathy and is responsible for high morbidity and mortality worldwide. Cortistatin is a neuropeptide produced by neurons and cells of the immune and vascular systems. Besides its action in locomotor activity and sleep, cortistatin inhibits inflammation in different experimental models of autoimmune diseases. However, its role in inflammatory cardiovascular disorders is unexplored. Here, we investigated the therapeutic effects of cortistatin in a well‐established preclinical model of experimental autoimmune myocarditis (EAM). Experimental Approach: We induced EAM by immunization with a fragment of cardiac myosin in susceptible Balb/c mice. Cortistatin was administered i.p. starting 7, 11 or 15 days after EAM induction. At day 21, we evaluated heart hypertrophy, myocardial injury, cardiac inflammatory infiltration and levels of serum and cardiac inflammatory cytokines, cortistatin and autoantibodies. We determined proliferation and cytokine production by heart draining lymph node cells in response to cardiac myosin restimulation. Key Results: Systemic injection of cortistatin during the effector phase of the disease significantly reduced its prevalence and signs of heart hypertrophy and injury (decreased the levels of brain natriuretic peptide) and impaired myocardial inflammatory cell infiltration. This effect was accompanied by a reduction in self‐antigen‐specific T‐cell responses in lymph nodes and in the levels of cardiomyogenic antibodies and inflammatory cytokines in serum and myocardium. Finally, we found a positive correlation between cardiac and systemic cortistatin levels and EAM severity. Conclusions and Implications: Cortistatin emerges as a new candidate to treat inflammatory dilated cardiomyopathy.